Compliance-Free ZrO2/ZrO2 − x /ZrO2 Resistive Memory with Controllable Interfacial Multistate Switching Behaviour - Ruomeng Huang; Xingzhao Yan; Sheng Ye; Reza Kashtiban; Richard Beanland; Katrina A. Morgan; Martin D. B. Charlton; C. H. (Kees) de Groot (Nanoscale Research Letters, 2017)
Abstract A controllable transformation from interfacial to filamentary switching mode is presented on a ZrO2/ZrO2 − x /ZrO2 tri-layer resistive memory. The two switching modes are investigated with possible switching and transformation mechanisms proposed. Resistivity modulation of the ZrO2 − x layer is proposed to be responsible for the switching in the interfacial switching mode through injecting/retracting of oxygen ions. The switching is compliance-free due to the intrinsic series resistor by the filaments formed in the ZrO2 layers. By tuning the RESET voltages, controllable and stable multistate memory can be achieved which clearly points towards the capability of developing the next-generation multistate high-performance memory.